Forecasting of solar radiation using fuzzy neural networks - Seng, Anthony Sunjaya. (2012)
The growing concern of scarcity of fuel and gas has been one of the main reasons for scientists and researchers to develop more effective and efficient alternative energy, like wind, solar, stream energy and nuclear energy. However, this report will only touch on one of the ways to improve the efficiency of using solar energy in generating power as an alternative power supply in power generation systems.